A Fibrosis‐Independent Hepatic Transcriptomic Signature Identifies Drivers of Disease Progression in Primary Sclerosing Cholangitis. Issue 3 (28th February 2021) - Gindin, Yevgeniy; Chung, Chuhan; Jiang, Zhaoshi; Zhou, Jing Zhu; Xu, Jun; Billin, Andrew N.; Myers, Robert P.; Goodman, Zachary; Landi, Abdolamir; Houghton, Michael; Green, Richard M.; Levy, Cynthia; et al.
Abstract : Background and Aims: Primary sclerosing cholangitis (PSC) is a heterogeneous cholangiopathy characterized by progressive biliary fibrosis. RNA sequencing of liver tissue from patients with PSC (n = 74) enrolled in a 96‐week clinical trial was performed to identify associations between biological pathways that were independent of fibrosis and clinical events. Approach and Results: The effect of fibrosis was subtracted from gene expression using a computational approach. The fibrosis‐adjusted gene expression patterns were associated with time to first PSC‐related clinical event (e.g., cholangitis, hepatic decompensation), and differential expression based on risk groups and Ingenuity Pathway Analysis were performed. Baseline demographic data were representative of PSC: median age 48 years, 71% male, 49% with inflammatory bowel disease, and 44% with bridging fibrosis or cirrhosis. The first principle component (PC1) of RNA‐sequencing data accounted for 18% of variance and correlated with fibrosis stage ( ρ  = −0.80; P  < 0.001). After removing the effect of fibrosis‐related genes, the first principle component was not associated with fibrosis ( ρ  = −0.19; P  = 0.11), and a semisupervised clustering approach identified two distinct patient clusters with differential risk of time to first PSC‐related event ( P  < 0.0001). The two groups had similar fibrosis stage, hepatic collagen content, and α‐smooth muscle actin expression by morphometry, Enhanced Liver Fibrosis score, and serum liver biochemistry, bile acids, and IL‐8 (all P  > 0.05). The top pathways identified by Ingenuity Pathway Analysis were eukaryotic translation inhibition factor 2 (eIF2) signaling and regulation of eIF4/p70S6K signaling. Genes involved in the unfolded protein response, activating transcription factor 6 ( ATF6 ) and eIF2, were differentially expressed between the PSC clusters (down‐regulated in the high‐risk group by log‐fold changes of −0.18 [ P  = 0.02] and −0.16 [ P  = 0.02], respectively). Clinical events were enriched in the high‐risk versus low‐risk group (38% [12/32] vs. 2.4% [1/42], P  < 0.0001). Conclusions: Removing the contribution of fibrosis‐related pathways uncovered alterations in the unfolded protein response, which were associated with liver‐related complications in PSC.